Cobot Kinematic Model for Industrial Applications - Giorgio Figliolini; Chiara Lanni; Luciano Tomassi (Inventions, 2025)
In this paper, a specific parametric and open-source algorithm for the direct and inverse kinematics of the UR5e Cobot is formulated by using the (n, o, a, p) transformation matrix, along with the inverse matrices, and then implemented in Matlab for numerical validation purposes. Thus, a specific robotized cell that includes novel mechatronic devices has been designed and built at LARM (Lab. of Robotics and Mechatronics) in Cassino in order to experimentally validate the proposed algorithm. In particular, many experimental points to carry out the whole automatic cycle have been detected by using the corresponding teach-pendant tool and joint positions for different UR5e Cobot poses. In addition, this consistent experimental campaign has allowed to evaluate the percentage accuracy of the robot, which can be useful for the practical applications. Therefore, the proposed kinematic model, along with the parametric and open-source algorithm, of the UR5e Cobot can be useful to simulate different applications in several robotized cells with a good reliability with respect to the real program of the robot.